Genetic diversity and relationship of Bugesera and Rwamagana indigenous chicken populations with SASSO chickens using DArTseq SNPs - Valentin Mujyambere; Kwaku Adomako; Martin Ntawubizi; Laetitia Nyinawamwiza; Judith Uwihirwe; Alexander Wireko Kena (PLoS ONE, 2025)
The genetic improvement of Rwandan indigenous chickens (IC) is becoming a priority and requires genetic characterization as the foundation for genetic improvement. The aim was to study the genetic diversity and relationship of IC from Bugesera and Rwamagana districts with SASSO chickens in Rwanda. Eighty-seven DNA samples were genotyped using Diversity Array Technology and generated 45,677 DArTseq SNPs. After the quality control, the genetic diversity and relationship were analyzed with dartR package, STRUCTURE and STRUCTURE Harvester. Only 8087 markers and 86 samples were remained for analysis. The high and low expected heterozygosity (He) were observed in Rwamagana (0.405) and SASSO (0.388) populations, respectively. The lowest difference was observed between SASSO and Rwamagana populations (0.018). The structure analysis separated IC (Cluster 1) from SASSO chickens (Cluster 2). Chickens from Rwamagana population were genetically related to SASSO indicating the uncontrolled crossbreeding. DArTseq SNPs were efficient and can be recommended for genomic studies in chickens.